2020
DOI: 10.1371/journal.pone.0244215
|View full text |Cite
|
Sign up to set email alerts
|

Detailed genetic and functional analysis of the hDMDdel52/mdx mouse model

Abstract: Duchenne muscular dystrophy (DMD) is a severe, progressive neuromuscular disorder caused by reading frame disrupting mutations in the DMD gene leading to absence of functional dystrophin. Antisense oligonucleotide (AON)-mediated exon skipping is a therapeutic approach aimed at restoring the reading frame at the pre-mRNA level, allowing the production of internally truncated partly functional dystrophin proteins. AONs work in a sequence specific manner, which warrants generating humanized mouse models for precl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…However, a recent study revealed that these humanized DMD mice carry two copies of the human DMD transgene at the integration locus in a tail-to-tail orientation, making this DMD mouse model unsuitable for testing in vivo CRISPR-Cas9 gene editing. 29 This is because the sgRNA can cut twice in the human DMD transgenes, which may generate unwanted chromosomal alterations, including large deletions, inversions, or translocations. In contrast, the humanized DMD mouse model created in this study contains mouse exon 51 replaced by its human ortholog within the endogenous genomic location on the X chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study revealed that these humanized DMD mice carry two copies of the human DMD transgene at the integration locus in a tail-to-tail orientation, making this DMD mouse model unsuitable for testing in vivo CRISPR-Cas9 gene editing. 29 This is because the sgRNA can cut twice in the human DMD transgenes, which may generate unwanted chromosomal alterations, including large deletions, inversions, or translocations. In contrast, the humanized DMD mouse model created in this study contains mouse exon 51 replaced by its human ortholog within the endogenous genomic location on the X chromosome.…”
Section: Discussionmentioning
confidence: 99%
“…Using a zebrafish reporter, we identified DG9 as a promising, novel PMO peptide conjugate that induced strong exon skipping in skeletal muscle and higher skipping in the heart ( 21 ). Here, we test the efficacy of DG9-conjugated exon skipping PMOs (DG9-PMOs) in dystrophic hDMDdel52; mdx mice, which have an integrated human DMD transgene in chromosome 5, with an out-of-frame partial deletion of exon 52 ( 22 , 23 ). These mice also have the mdx mutation, a nonsense point mutation in exon 23 of the mouse Dmd gene ( 24 ), and so do not have detectable human or mouse dystrophin.…”
mentioning
confidence: 99%
“…All animal experiments were approved by the Animal Care and Use Committee, University of Alberta Research Ethics Office (AUP00000365). Genotypes were confirmed by PCR [ 20 , 21 , 22 ]; only male mice that were heterozygous for the human exon 52-deleted DMD transgene were used for analysis. Mice received standard food and water ad libitum.…”
Section: Methodsmentioning
confidence: 99%
“…This model contains a full-length, human DMD transgene on one copy of chromosome 5 with an out-of-frame partial deletion of exon 52. Due to the location of the deletion, only the expression of dystrophin isoforms with promoters downstream of exon 52 is permitted—in the case of muscle, this would be Dp71 [ 20 , 21 , 22 ]. Moreover, as this transgene is on a wild-type background (del52;WT), this leads to an overexpression model where the Dp71 protein comes from both human and murine sources.…”
Section: Introductionmentioning
confidence: 99%